Foreign Language Instructors’ Professional Development in Times of Crisis: Challenges and Solutions - Bailey, Angela C; Corrales, Kathleen A.; Rey-Paba, Lourdes; Rosado-Mendinueta, Nayibe (Íkala, Revista de Lenguaje y Cultura, 2022)
The unprecedented situation of COVID-19 compelled many universities and colleges worldwide to reconsider both the management and delivery of classes, forcing faculty to use innovative online and mobile means. The transition also caused faculty to reevaluate their professional development (PD). This qualitative exploratory study focused on the PD experienced by a group of foreign language university instructors in Colombia during this crisis. Specifically it identified the challenges encountered and how these were tackled. Data were collected through an open-ended survey and analyzed using content analysis. Results show ten main challenges, which were then categorized into three themes: (a) adaptation to emergency remote teaching, (b) promotion of student engagement, and (c) handling of emotions. Conclusions reveal that professors embraced the crisis with a positive attitude, engaging in different PD opportunities, displaying agency, responsibility, and flexibility. Therefore, the challenges and their reaction to them fostered their PD and learning. These findings suggest that institutions should allow instructors to give input into the types of PD programs that they need forspecific situations.